Use of information sources in outbound travel planning: case of the Netherlands and Belgium - Medne, Ilze; Berzina, Kristine (University of Latvia, 2020)
In the Information Age travellers have a wide range of information that can be accessed by a variety of channels. The kind of information search travellers undertake and acquire will have significant consequences for the purchases they will make. There is a need for repeated studies to track possible changes in tourist behaviour for information search patterns as use of information sources and their combination evolve over the time. Understanding tourists’ information search peculiarities can be of use for tourism scholars and practitioners in the marketing planning process. Majority of European citizens are travelling mainly within their home country (Eurobarometer, 2014) still small countries of Central Europe are among the most active international travellers (Eurostat, 2018). The aim of the research is to study the usage of sources of information and their combinations in outbound travel planning for Dutch and Belgian travellers. The research is based on the data of a survey of travelling population carried out in different cities of the Netherlands and Belgium in the summer 2018. 502 valid questionnaires were obtained. MS Excel, SPSS and R network visualization visNetwork software tools were used for analysing the data applying following methods - descriptive statistics, crosstabulation and network analysis method concept as network diagram. The conclusions and recommendations of the study are addressed to marketing organizations of tourism destinations and companies, whose target market is tourists from Belgium and the Netherlands.
Keywords: travel planning; information sources; experience; social media